1997
DOI: 10.1161/01.cir.95.6.1366
|View full text |Cite
|
Sign up to set email alerts
|

Increased Restenosis in Diabetes Mellitus After Coronary Interventions Is Due to Exaggerated Intimal Hyperplasia

Abstract: Serial IVUS analysis showed that the main reason for increased restenosis in diabetes mellitus was exaggerated intimal hyperplasia in both stented and nonstented lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
207
1
8

Year Published

1999
1999
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(222 citation statements)
references
References 14 publications
6
207
1
8
Order By: Relevance
“…Until now, there are only few studies giving insight into the role of diabetes on vascular remodeling and plaque accumulation in stenotic and nonstenotic coronary vessels [33,34]. In these studies, limited vessel remodeling could be demonstrated, but seemed to be confined to patients with type 1 diabetes.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Until now, there are only few studies giving insight into the role of diabetes on vascular remodeling and plaque accumulation in stenotic and nonstenotic coronary vessels [33,34]. In these studies, limited vessel remodeling could be demonstrated, but seemed to be confined to patients with type 1 diabetes.…”
Section: Study Limitationsmentioning
confidence: 99%
“…[1][2][3][4] Studies in affected patients as well as animal models have suggested that the inflammatory and proliferative responses are enhanced in diabetes and may explain the observed increased restenosis rate. [5][6][7][8] Pathological analyses indicate that neointimal formation is characterized by an inflammatory reaction at the site of injury, migration and proliferation of vascular smooth muscle cells (VSMCs), and the synthesis of excess matrix. Despite the well-defined nature of the lesion, the pathogenic mechanisms leading to exaggerated restenosis remain largely undefined.…”
mentioning
confidence: 99%
“…In addition to the classic risk factors for in-stent restenosis, including multivessel disease, small-diameter vessels, long lesions, and bifurcations, recent IVUS studies have demonstrated that excessive arterial remodeling at preintervention, 11 large plaque burden before or after intervention, 12 and diabetes mellitus 13 should be also segregated for their biologically active milieus. After intracoronary brachytherapy as the first biological vector to approach those high-risk lesions, stentbased local drug delivery is considered an emerging breakthrough technology with less technical demand for operators.…”
Section: Discussionmentioning
confidence: 99%